PEMBERDAYAAN MITRA PEMELIHARAAN Holothuriascabra - Santi Penina Tua Rahantoknam; Syahibul Kahfi Hamid; Kristhina Priskila Rahael (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
Good economic prospects of H. scabra cause H. scabra to be captured for sale without regard to the sustainability of H. scabra. Initially the partners only captured H. scabra and sold it to collectors. The presence of H. scabra which is starting to be difficult to obtain encourages partners to start an enlargement effort. The existing condition of the enlargement business carried out by the partners is still conventional, the absence of a good application of science and technology causes the results obtained by partners have not been maximized. The main purpose of this activity is to empower partners in the enlargement of H. scabra with the application of good science and technology in feeding. The method of implementing community service (partners) to solve the problems experienced by partners in the enlargement of H. scabra is by training. The main work of this science and technology implementation activity is the training of partners in preparing and feeding H. scabra enlargement. The advantage of training feeding strategies is that partners can increase H. scabra production. Partners are able to know the growth of H. scabra and know the harvest time of H. scabra. Training and mentoring during the implementation of this program received good appreciation from partners, partners have better knowledge and skills in enlargement of H.scabra especially in H. scabra feeding and are skilled in measuring growth.